Influencing factors of health inequality among urban elderly in China: a RIF-I-OLS decomposition analysis - Jing YANG; Lian-you LI; Chang-jian PAN (Editorial Office of Chinese Journal of Public Health, 2022)
Objective To examine factors affecting health inequality of urban elderly in China and to provide evidences for promoting equality in healthy aging. MethodsThe data on 16170 urban elderly aged ≥ 65 years were extracted from Chinese Longitudinal Healthy Longevity Survey (CLHLS) conducted yearly from 2005 to 2018. Health inequality and its changing trend among the elderly were comprehensively assessed with mobility scale, physical activity scale, social activity scale, and symptom-problem complexity scale. Recentered influence function-index-ordinary least squares (RIF-I-OLS) decomposition method was used to analyze influencing factors of health inequality among the elderly. Results Among the elderly surveyed, the average score for quality of well-being scale increased from 0.66 in 2005 to 0.72 in 2018. An income-related health inequality was observed among the elderly and the Wagstaff's index (WI) and Erreygers's index (EI) for health inequality fluctuated over time, decreasing from 0.0269 and 0.0258 in 2005 to 0.0225 and 0.0207 in 2018, indicating that individuals at younger ages were more likely to have health inequality compared to the elderly at old ages. All the results of regression analysis on influencing factors for the four-category health inequality indexes obtained by the RIF-I-OLS decomposition method demonstrated that total medical expense in previous one year, availability of timely medical treatment for major disease, and self-supported living at older age were protective factors against the health inequality; whereas, disparities in age/education/family medical payment ratio, pension inequality, and differentiation of current physical activity could exacerbate the health inequality among the urban elderly.ConclusionAmong urban elderly in China, unequal socioeconomic status is an incentive factor for health inequality; promotion in the fairness and efficiency of medical health system, household's reduction in disease burden, and improvement in the redistribution of pension system may buffer and compensate the health inequality.